Estimating the willingness to pay for a sustainable wine using a Heckit model - Ricardo Sellers Rubio; Juan Luis Nicolau-Gonzalbez (Wine Economics and Policy, 2016)
Sustainability is an important challenge for wineries. Although sustainability represents a way to differentiate wines and to meet some market segment demands, it also constitutes a necessary strategy to guarantee the future development of the wine sector. However, some wineries state that production costs are higher for sustainable wines than for conventional wines. Thus, the goal of this paper is to analyze the premium price that consumers are willing to pay for a sustainable wine with respect to the price of a conventional wine with similar characteristics. An experiment based on contingent valuation was designed to test the differences in the willingness to pay for sustainable wines among market segments. Further, a Heckit model was estimated, which avoids the problems of the methodologies applied to date. Results reveal that most consumers are willing to pay a higher price for sustainable wines, and that there are differences among the main market segments. In addition, several variables regarding socio-economic characteristics of the consumer (age, gender and income) affect the willingness to pay. Results show that as consumers' knowledge increases, willingness to pay a premium decreases and that consumers that are more concerned about the environment are willing to pay a higher premium.
Keywords: 330; Heckit; Sustainability; Willingness-to-pay